Idiopathic pulmonary haemosiderosis: an unusual case of anaemia with pulmonary involvement - Khan, Momina; Gowa, Murtaza Ali; Jamal, Ghazala; Nawaz, Hira; Abidi, Syed Muhammad Aqeel (Journal of the Pakistan Medical Association, 2023)
Idiopathic pulmonary haemosiderosis is a rare disorder, with recurrent life-threatening alveolar haemorrhages and chronic lung parenchymal changes. It is associated with a triad of haemoptysis, iron deficiency anaemia, and diffuse pulmonary infiltrates. Although most cases are idiopathic, secondary haemosiderosis linked to known diseases has also been observed. Most of the cases remain undiagnosed because the disease is very low on the list of differentials. There is no specified age for the disease. The present study reports on an adolescent female patient who presented with microcytic anaemia and bilateral lung infiltrates to the National Institute of Child Health (NICH), Karachi, a tertiary care hospital. She was diagnosed with Idiopathic pulmonary haemosiderosis after ruling out other possibilities. Keywords: Pulmonary haemosiderosis, Alveolar haemorrhages, Lung disease, Alveolar hypoventilation syndrome.